Seed transmission characteristics of selected bean common mosaic virus strains in differential bean cultivars - Morales, Francisco José; Castaño, M. (Scientific Societies, 1987)
One necrosis-inducing strain and four mosaic-inducing strains of bean common mosaic virus (BCMV) were differentially seed-transmitted in 14 mosaic-susceptible bean (Phaseolus vulgaris) cultivars. Dubbele Witte, Redlands Greenleaf B, Michelite, Sanilac, and Red Mexican 35 consistently transmitted the US 1, US 2, US 5, NL 3, and NL 4 strains of BCMV in 39.7 54.4% of the seed produced by infected plants. On the contrary, Imuna and the Great Northern lines 31 and 123 transmitted the virus in less than 1% of the seed tested. Pinto 114 did not transmit BCMV US 2 in tests involving more than 1,000 seeds. Maximum seed transmission rates were observed for test plants inoculated at the primary leaf stage. Twelve of 14 cultivars tested did not transmit any of the selected BCMV strains in seeds of plants inoculated 30 days after sowing. Number and weight of seeds produced by test plants inoculated at the primary leaf stage were reduced in relation to the same yield components analyzed for bean plants inoculated 20 days later. The necrosis-inducing BCMV NL 3 strain proved highly transmissible in the seed of the navy cultivars Sanilac and Michelite commonly cultivated in regions where this necrotic BCMV strain constitutes a production problem.